Ponseti Technique is the Best Option for the Treatment of Idiopathic Congenital Club Foot by the Age of Two Years - Rahman, Md Mostafizur; Islam, Shafiqul; Rouf, Abdur; Momen, Md Abdul; Islam, Md Zahidul; Ohab, Md Abdul; Rahman, Md Ashfaqur; Shaha, Bablu Kumar (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Club foot is the commonest congenital deformity in babies. Around 80% of the cases occur in developing nations. There are many option for treating club foot, Ponseti technique is one of them. This prospective interventional study was carried out at the Department of Orthopaedic & Traumatology, Rangpur Medical College Hospital, over period of 3 year from 22/09/2011 to 22/12/2014. One hundrad and Fifty patients of two hundrads and twenty three foots were treated by ponseti technique and followed up for the purpose of this study. Both rigid and non rigid variety of club foot were treated irrespective of sex and side of foot involvement. Pirani scoring system was used to assess the severity of deformity, needs of tenotomy and evaluation of result. All the patients were treated by Ponseti technique, only 83 (11.1%) foot by plaster, 140 (88.9%) foot required tenotomy. There were complication of 29 (13%) foot of 19 patients in the form of plaster sore. All patients were under bracing protocol. In this study it is found that 94.61% satisfactory result. So Ponseti technique is a safe, effective & low cost and easily acceptable. So it is the best option for the treatment of idiopathic congenital club foot under the age of two years. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 27-30